2011
DOI: 10.1007/s00198-011-1534-0
|View full text |Cite
|
Sign up to set email alerts
|

Fracture liaison services for the evaluation and management of patients with osteoporotic fracture: a cost-effectiveness evaluation based on data collected over 8 years of service provision

Abstract: FLSs are cost-effective for the prevention of further fractures in fragility-fracture patients. The cost of widespread adoption of FLS across the UK is small in comparison with other service provision and would be expected to result in important benefits in fractures avoided and reduced hospital bed occupancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
130
0
14

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(149 citation statements)
references
References 11 publications
4
130
0
14
Order By: Relevance
“…The choice of cutoff must be based on an overall assessment of the morbidity from the screened disease, the prevalence and the risk from further investigation. If orthopedic surgeons use 4 cm as cutoff point to select the patients for a DXA, then 6 of 10 patients will unnecessarily undergo DXA, however, in view of the morbidity associated with osteoporosis and future fracture risk in relation to the risk and cost of DXA, this seems reasonable [13].…”
Section: Resultsmentioning
confidence: 99%
“…The choice of cutoff must be based on an overall assessment of the morbidity from the screened disease, the prevalence and the risk from further investigation. If orthopedic surgeons use 4 cm as cutoff point to select the patients for a DXA, then 6 of 10 patients will unnecessarily undergo DXA, however, in view of the morbidity associated with osteoporosis and future fracture risk in relation to the risk and cost of DXA, this seems reasonable [13].…”
Section: Resultsmentioning
confidence: 99%
“…The FLS model of care has also been subject to cost-effectiveness modelling. An example of this approach is a cohort health-state transition model (a Markov model) developed to evaluate the Glasgow FLS in Scotland, UK [37]. The model demonstrated that 18 fractures were prevented, including 11 hip fractures, and £21,000 (€26,250, US$30,000) was saved per 1,000 patients managed by the Glasgow FLS vs 'usual care' in the UK.…”
Section: Secondary Fracture Preventionmentioning
confidence: 99%
“…5 Primary prevention in those who have not fractured is controversial, 6 except perhaps when considering prevention of medication-induced bone fragility, particularly that associated with glucocorticoids. 7 The three most commonly used treatment thresholds when considering secondary fracture prevention are: low bone density, thresholds devised by NOGG that vary with age, and fixed treatment thresholds.…”
Section: Splmentioning
confidence: 99%